Deciphering the genetics and mechanisms of predisposition to multiple myeloma - Went, Molly; Duran-Lozano, Laura; Halldorsson, Gisli H.; Gunnell, Andrea; Ugidos-Damboriena, Nerea; Law, Philip; Ekdahl, Ludvig; Sud, Amit; Thorleifsson, Gudmar; Thodberg, Malte; Olafsdottir, Thorunn; Lamarca-Arrizabalaga, Antton; et al. (Nature Communications, 2024)
Multiple myeloma (MM) is an incurable malignancy of plasma cells. Epidemiological studies indicate a substantial heritable component, but the underlying mechanisms remain unclear. Here, in a genome-wide association study totaling 10,906 cases and 366,221 controls, we identify 35 MM risk loci, 12 of which are novel. Through functional fine-mapping and Mendelian randomization, we uncover two causal mechanisms for inherited MM risk: longer telomeres; and elevated levels of B-cell maturation antigen (BCMA) and interleukin-5 receptor alpha (IL5RA) in plasma. The largest increase in BCMA and IL5RA levels is mediated by the risk variant rs34562254-A at TNFRSF13B. While individuals with loss-of-function variants in TNFRSF13B develop B-cell immunodeficiency, rs34562254-A exerts a gain-of-function effect, increasing MM risk through amplified B-cell responses. Our results represent an analysis of genetic MM predisposition, highlighting causal mechanisms contributing to MM development.